The vertigo years Europe, 1900 - 1914 - Blom, Philipp 1970- (Basic Books, 2008)
Examines how changes from the Industrial Revolution prior to World War I brought about radical transformation in society, changes in education, and massive migration in population that led to one of the bloodiest events in history.
Includes bibliographical references (p. 426-452) and index
Keywords: Geschichte 1900-2000; Sozialgeschichte 1900-1914; Changement social - Europe - 20e siècle; Geschichte; Social change -- Europe -- History -- 20th century; Europe - 1871-1918; Europe - Civilisation - 20e siècle; Europe - Conditions sociales - 20e siècle; Europe - History - 1871-1918; Europa; Europe -- History -- 1871-1918; Europe -- Civilization -- 20th century; Europe -- Social conditions -- 20th century